Синтез, антиексудативна та антимікробна активність 6-арилідензаміщених імідазо[2,1-b]тіазолів - Saliyeva, Lesya M.; Holota, Serhii M.; Grozav, Alina M.; Yakovychuk, Nina D.; Lukashchuk, Mykola M.; Marushko, Larysa P.; Slyvka, Nataliia Yu.; Vovk, Mykhailo V. (National University of Pharmacy, 2021)
Aim. To expand the range of 6-arylidene-2-methyl-2,3-dihydroimidazo[2,1-b]thiazolones as potential objects for studying the antiexudative and antimicrobial activities. Results and discussion. It has been shown that the condensation of synthetically affordable 2-methyl-2,3-dihydroimidazo[2,1-b]thiazolone with aromatic aldehydes can be successfully used for obtaining the corresponding 6-ylidene-functionalized derivatives. The biological screening of the compounds synthesized revealed that they possessed a low or moderate anti-inflammatory activity and inhibited the inflammation process in the range from 3 to 44 %. During the study of the antimicrobial activity of the substances obtained it was determined that their minimum bacteriostatic and minimum fungistatic concentrations ranged from 31.25 to 250 μg/mL. Experimental part. The interaction of 2-methyl-2,3-dihydroimidazo[2,1-b]thiazolone with a series of benzaldehydes and salicylic aldehydes in refluxing acetic acid in the presence of anhydrous sodium acetate leads to new 6-arylidene-2-methyl-2,3-dihydroimidazo[2,1-b]thiazolones. The antiexudative activity screening was performed on the model of carrageenan-induced paw oedema of white outbred male rats. The antimicrobial activity of the compounds was studied using the microtechnique of two-fold serial dilutions in a liquid nutrient medium. Conclusions. It has been found that the Knoevenagel condensation of 2-methyl-2,3-dihydroimidazo[2,1-b]thiazolone with aromatic aldehydes is a convenient way for the structural modification of the position 6 of the heterocyclic system by the arylidene moiety. The arylidene derivatives obtained show a moderate antiexudative activity in the carrageenan-induced rat paw oedema assay, as well as the antimicrobial activity against some gram-positive and gram-negative bacteria and fungi.